Developmental trajectory of hope among late-adolescents: Population heterogeneity and the impact of gender and family socioeconomic status. (April 2019) - Yin, Xiayun; Li, Zhihua; Yuan, Yanyun; Wang, Zhihang
Abstract: Objective: To study the developmental trajectory of hope among late-adolescents, taking population heterogeneity and the impact of gender and family socioeconomic status (SES) into consideration. Methods: The study used the Snyder Hope Scale to perform four surveys of a sample of 381 Chinese late-adolescents, both male and female, with a mean age of 17.69 ± 1.12 years, over the course of one year, and employed a growth mixture model to perform data analysis. Results: Although the levels of hope among the respondents who had high and moderate levels of hope at the outset of the study remained relatively stable over the course of the year, those with low levels of hope exhibited a significant decrease over time. Conclusions: There is significant population heterogeneity in late-adolescents' developmental trajectory of hope. Additionally, gender and family SES have a significant effect on the developmental trajectory of hope, as significantly more female students than male students reported high levels of hope. Furthermore, participants with high family SES outnumbered those with low family SES in the high-hope group, whereas those with low SES outnumbered those with high SES in the low-hope group.